Proton Pump Inhibitor Use before Percutaneous Endoscopic Gastrostomy Is Associated with Adverse Outcomes - Im, Jong Pil (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Pancreatobiliary Association; Korean Society of Gastrointestinal Cancer, 2014)
BACKGROUND/AIMS: Knowledge of the risk factors associated with adverse outcomes after percutaneous endoscopic gastrostomy (PEG) may be helpful for developing PEG recommendations. The purpose of this study was to identify the clinical risk factors associated with adverse clinical outcomes after PEG, especially regarding the use of proton pump inhibitors (PPIs). METHODS: We retrospectively reviewed the data from PEG patients at seven university hospitals between June 2006 and January 2012. All patients were followed up through February 2012 after PEG, and the clinical risk factors for adverse clinical outcomes after PEG were analyzed. RESULTS: Data from 1,021 PEG patients were analyzed. PPI users were more frequently included in the complication group than the noncomplication group (p=0.040). PEG-related complications (p=0.040) and mortality (p=0.003) were more frequent in the PPI group than in the control group. In the subgroup analysis of complicated PEG cases, infectious complications were more frequently found in the PPI group than in the control group (35.8% vs 27.8%). After adjustment for multiple possible confounding factors, PPI users (odds ratio, 1.531; 95% confidence interval, 1.017 to 2.305) and diabetic patients had increased mortality after PEG. CONCLUSIONS: PPI use may be associated with adverse outcomes in patients with PEG; however, further prospective studies investigating this issue are warranted.